Garlic and Onion Attenuates Vascular Inflammation and Oxidative Stress in Fructose-Fed Rats - Marcela Alejandra Vazquez-Prieto; Cecilia Rodriguez Lanzi; Carina Lembo; Claudio Rómulo Galmarini; Roberto Miguel Miatello (Journal of Nutrition and Metabolism)
This study evaluates the antioxidant and the anti-inflammatory properties of garlic (G) and onion (O) in fructose-fed rats (FFR). Thirty-day-old male Wistar rats were assigned to control (C), F (10% fructose in drinking water), F+T (tempol 1 mM as control antioxidant), F+G, and F+O. Aqueous G and O extracts were administered orally in doses of 150 and 400 mg/kg/d respectively, and along with tempol, were given during the last 8 weeks of a 14-week period. At the end of the study, FFR had developed insulin resistance, aortic NADPH oxidase activity, increased SBP, plasma TBARS and vascular cell adhesion molecule-1 (VCAM-1) expression in mesenteric arteries, and a decrease in heart endothelial nitric oxide synthase (eNOS). Garlic and onion administration to F rats reduced oxidative stress, increased eNOS activity, and also attenuated VCAM-1 expression. These results provide new evidence showing the anti-inflammatory and antioxidant effect of these vegetables.